Centralizers of linear and locally nilpotent derivations
UDC 512.715, 512.554.31 Let K be an algebraically closed field of characteristic zero, K[x_1,…,x_n] be the polynomial algebra and W_n(K) be the Lie algebra of all K-derivations on K[x_1,…,x_n]. For any derivation D with linear components, we describe the centralizer of D in W_n(K), and propose an algorithm for finding the generators of this centralizer regarded as a module over the ring of constants of the derivation D in the case where D is a basic Weitzenboeck derivation. In a more general case where a finitely generated integral domain A over the field K is considered instead of the polynomial algebra K[x_1,…,x_n] and D is a locally nilpotent derivation on A, we prove that the centralizer C_Der A